SOCIAL EMOTIONAL LEARNING PROGRAM FOR BUILD RESPONSIBLE CHARACTER OF STUDENTS IN ELEMENTARY SCHOOL - Farah Adiba, Lu’lu’a Farah Adiba; Latip, Asep Ediana (JMIE (Journal of Madrasah Ibtidaiyah Education), 2021)
The aim of this research was describe Social Emotional Learning (SEL) Program for build responsible character of students in elementary school. The approach for this study was qualitative. The main method of this study was library research that supported with filed research. Library research that referred in this study was an activity to collected data, read, took notes, and processed the data that related with Social Emotional Program in Schools. It was obtained from books, journals, and articles. There are 5 main journals supported by 10 other. The researcher was collected the data from documents, research notes, and interviews. The interviewees are people who have direct contact with Social Emotional Program such as Head of Social Emotional Program Department, teachers, students and parents of Kharisma Bangsa Elementary School. This study used purposive sampling technique. The instruments of this research were document check list, notes, and interview guidelines. Data analysis was achieved through a content analysis technique. The result showed that Social Emotional Learning Program can build responsible character of students in elementary school. It can be obtained by growing social awareness, self-management, self-awareness, responsible decision making, and relationship skills after implementing Social Emotional Learning Program. The Social Emotional Learning Program was effective to build the responsibility by using some approaches there were Explicit SEL Instruction, Teacher Instructional, and Integrated with curriculum areas that supported by several strategies between PATH, RC, 4R’s, and RULER.